PERAN LEMBAGA PEMASYARAKATAN DALAM MENINGKATKAN KUALITAS HIDUP KELOMPOK RENTAN LANJUT USIA DAN PENGIDAP PENYAKIT KRONIS - Subroto, Mitro; Indrawan, M. Fajar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: This research examines the role of correctional institutions in enhancing the quality of life for vulnerable groups, specifically the elderly and individuals with chronic illnesses. The urgency of this study arises from the increasing number of elderly inmates and those suffering from chronic diseases, necessitating improved rehabilitation strategies. Employing a qualitative research method, data were collected through interviews and observations within selected correctional facilities. The findings reveal that tailored health services and social support systems significantly contribute to better health outcomes and overall well-being for these groups. This study underscores the importance of integrating health care and social services in correctional settings to foster rehabilitation and improve life quality among vulnerable populations. Keywords: correctional institutions; vulnerable groups; elderly; chronic illness; quality of life.